DEVELOPMENT OF COOPERATIVE INSTITUTIONS IN KALANGANYAR VILLAGE, SEDATI DISTRICT, SIDOARJO DISTRICT - Casmiwati, Dewi; Lubis, Lunariana; Azari, Chasan (UNIVERSITAS SERAMBI MEKKAH, 2024)
The women's cooperative in Kalanganyar Village, Sedati District, Sidoarjo Regency is currently not running optimally. From the survey results it is known that Cooperatives are financed by the government and before the Pandemic had various activities including Savings and Loans. However, with Covid 19 in 2020, these existing activities stopped. After examining several institutional problems that arise in the Cooperative, namely. Cooperatives do not have effective management, doctrine, programs and extensive cooperation. Cooperatives do not have harmonious communication with the Kelurahan. The solutions offered are. Introducing cooperative institutional development by rearranging management in the organizational structure, jointly agreeing on doctrines and programs and building cooperation. Hold a meeting with the municipality. The goal: revive the existence of the Women's Cooperative. The method used is through socialization, personal approach, deliberation and assistance to the management of the Cooperative and the Kelurahan. Evaluation is carried out by looking at the development of the Women's Cooperative in carrying out its program. The result is that the Women's Cooperative is more open in formulating new management, agreeing on doctrines, programs and cooperation with external parties. The next step is to carry out ongoing assistance and monitoring.